Pengaruh Penambahan Ekstrak Bunga Telang (Clitoria ternatea L.) Terhadap pH, Kadar Alkohol dan Antioksidan kefir Susu Kambing - Gymnastiar, Muhammad Galih; Wulandari, Eka; Pratama, Andry (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Goat milk kefir is a fermented milk product that contains vitamins, minerals, and essential amino acids that can help maintain and improve body functions. In addition, kefir has anticancer, anti-inflammatory, and antidiabetic properties. Kefir can be made by adding telang flower extract (Clitoria ternatea L.) which aims to improve the characteristics and quality and add functional value to goat milk kefir. The study was conducted to determine the effect of the addition of telang flower extract on the characteristics of pH value, alcohol content, and antioxidant activity of goat milk kefir. This study used an experimental method with a completely randomised design (CRD), up to 4 concentration treatments (P1 = 0.5%, P2 = 1%, P3 = 1.5% and P4 = 2%) and repeated 5 times. The data on pH, alcohol content and antioxidant activity were analysed by analysis of variance, followed by Duncan's post hoc test. The results of the study identified that the addition of telang flower extract in making goat milk kefir gave the same effect on pH value and alcohol content. However, it increased the antioxidant activity. Based on this study, the addition of 1.5% telang flower extract produced the best treatment with a pH value of 4.30, alcohol content of 0.4% and antioxidant activity of 22.704 ppm.